Learning autonomy in the system of multilingual education - Volkova, G. K.; Wieler, G. O.; Волкова, Галина Костянтинівна; Вілер, Ганна Олександрівна (My University, 2022)
Abstract. The article deals with the development of personal quality which is the basis of “lifelong” learning. The main factors that contribute to the formation and development of educational autonomy are various forms of distance work, resource centers for independent work, continuous language education, work with educational projects, research, learning in the form of problem solving, language learning assessment.
Keywords: foreign language; lifelong education; learning strategies; learning autonomy; autonomous learning activity